1997
DOI: 10.1097/00007632-199707010-00019
|View full text |Cite
|
Sign up to set email alerts
|

The Prognosis of Low Back Pain in General Practice

Abstract: Only a few variables appear to be related to the clinical course of low back pain seen in general practice. In particular, the duration preceding the initial visit and, unexpectedly, receiving physical therapy were both associated with a longer duration of low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(75 citation statements)
references
References 16 publications
1
69
0
4
Order By: Relevance
“…Therefore, it is plausible that our study population represents workers with new episodes of low-back pain in these occupational health services. Due to this restriction of duration of sick leave at inclusion we could not study this factor, which was found to be an important prognostic factor in other studies (6).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, it is plausible that our study population represents workers with new episodes of low-back pain in these occupational health services. Due to this restriction of duration of sick leave at inclusion we could not study this factor, which was found to be an important prognostic factor in other studies (6).…”
Section: Discussionmentioning
confidence: 94%
“…However, in spite of the magnitude of the problem, little is known about the course of and prognostic factors for low-back pain among sick employees. Most studies about this topic concern patients in general practice or patients in a rehabilitation center, and the results will differ from those involving workers on sick leave with low-back pain who visit their occupational physicians (5,6). Patients with chronic low-back pain in primary care usually have little sickness absence, and patients from a rehabilitation center form a selection of more problematic cases (7).…”
mentioning
confidence: 99%
“…27 The analyses were adjusted for baseline values and for health insurance (which differed between the 2 groups at baseline). 28 The analyses of pain and physical functioning also were adjusted for potential prognostic variables based on the literature (ie, sex, 29,30 duration of the current episode of back pain, 31 previous back pain episode [s], 32 and education 33 ). All multilevel analyses were performed with MLwiN (version 1.10).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our data confirm that patients' subjective estimation of pain and disability already displays a prognostic value for therapy outcome that cannot be increased significantly by the assessment of physical parameters [50,53]. This finding makes it questionable whether the administrative burden associated with the assessment of somatic parameters and the conduct of performance tests is worth the small increase in predictability.…”
Section: C) D)mentioning
confidence: 53%